Transmission of Klebsiella strains and plasmids within and between grey‐headed flying fox colonies. (25th May 2022) - Vezina, Ben; Judd, Louise M.; McDougall, Fiona K.; Boardman, Wayne S. J.; Power, Michelle L.; Hawkey, Jane; Brisse, Sylvain; Monk, Jonathan M.; Holt, Kathryn E.; Wyres, Kelly L.
Summary: The grey‐headed flying fox ( Pteropus poliocephalus ) is an endemic Australian fruit bat, known to carry zoonotic pathogens. We recently showed they harbour bacterial pathogen Klebsiella pneumoniae and closely related species in the K . pneumoniae species complex ( Kp SC); however, the dynamics of Kp SC transmission and gene flow within flying fox colonies are poorly understood. High‐resolution genome comparisons of 39 Kp SC isolates from grey‐headed flying foxes identified five putative strain transmission clusters (four intra‐ and one inter‐colony). The instance of inter‐colony strain transmission of K . africana was found between two flying fox populations within flying distance, indicating either direct or indirect transmission through a common food/water source. All 11 plasmids identified within the Kp SC isolates showed 73% coverage (mean) and ≥95% identity to human‐associated Kp SC plasmids, indicating gene flow between human clinical and grey‐headed flying fox isolates. Along with strain transmission, inter‐species horizontal plasmid transmission between K . pneumoniae and Klebsiella africana was also identified within a flying fox colony. Finally, genome‐scale metabolic models were generated to predict and compare substrate usage to previously published Kp SC models, from human and environmental sources. These models indicated no distinction on the basis of metabolic capabilities. Instead, metabolic capabilities were consistent with population structure and ST/lineage.